Role of adiponectin gene variants, adipokines and hydrometry-based percent body fat in metabolically healthy and abnormal obesity. (January 2018) - Chang, Chin-Sung; Lu, Yan-Jia; Chang, Hsiu-Hao; Hsu, Shih-Han; Kuo, Po-Hsiu; Shieh, Chi-Chang; Yao, Wei-Jen; Hsu, Mei-Chi; Young, Kung-Chia; Lin, Wen-Yuan; Huang, Kuo-Chin; Wu, Chih-Hsing; et al.
Summary: Objective: Metabolically healthy obesity (MHO) subjects have better metabolic parameters than metabolically abnormal obesity (MAO) subjects, but the possible mechanisms underlying this remain unknown. Our study was designed to investigate the interrelationships among genes, adipokines, body fat and its distribution in MHO and MAO. Methods: From 2007 to 2009, 103 males and 131 females aged 18–50 years were enrolled by an intention-to-treat design in a weight management clinic. Participants were divided into MHO and MAO groups. Percent body fat (PBF) was measured by a deuterium oxide dilution method. Four polymorphic variants, including PPARγ2 (Pro12Ala and C1431T) and adiponectin (T45G and G276T) genes, and three adipokines (adiponectin, leptin and resistin) were obtained. Results: Of the 234 obese subjects, 130 (55.6%) were MHO. In the univariate analysis, the MAO group has significantly higher anthropometric, metabolic indices and leptin levels than the MHO group. Logistic regression analysis revealed that age, male gender, the T allele of adiponectin T45G polymorphism, leptin and PBF were positively associated with MAO. ANCOVA analysis revealed that the T allele of adiponectin T45G polymorphism was associated with higher fasting and postprandial glucose levels. We further found that TT genotype has a lower high molecular weight (HMW)/low molecular weight (LMW) adiponectin ratio than GG genotype. Conclusions: The factors associated with MAO are age, male gender, the T allele of adiponectin T45G polymorphism, leptin, and PBF. The net effects of T45G polymorphism on the MAO phenotype may be achieved by changes in the adiponectin oligomer ratio and glucose levels.